Strategies and Priorities for African Agriculture - Diao, Xinshen (2012)
Strategies and Priorities for African Agriculture Panel Discussion at IFPRI 3 October 2012 by Xinshen Diao, Deputy Division Director, Development Strategy and Governance Division, IFPRI.